Start-up nation the story of Israel's economic miracle - Senor, Dan; Singer, Saul.; Council on Foreign Relations (New York Twelve, 2009)
"What the world can learn from Israel's meteoric economic success."--Provided by the publisher.
Introduction -- Persistance -- Battlefield entrepreneurs -- The people of the book -- Harvard, Princeton and Yale -- Where rigid order meets random chaos -- Leap-frog : a short history of economic policy -- Immigration : the google guys' challenge -- Diaspora : stealing airplanes -- The buffett test -- Yozma : the match -- The birth of Israel's military industrial complex -- The life of Israel's cluster -- The death of Israel's military industrial complex & the birth of Israel's mashup complex -- A perpetuum mobile? : threats to the economic miracle -- Conclusion.
"A Council on Foreign Relations book."
Keywords: Israel -- Economic conditions